(3TQM bUjOI GdgGOi Hf EHQGgje Hf GdhRjQs - (3GdgGOj Hf EHQGgje Hf Ydj Hf GdeQJVj GdMSjfj Hf GdhRjQ,LeGd GdOjf , GHf GdhRjQ, J (B822 (3g` s; (3GdgGOj Hf EHQGgje Hf Ydj Hf GdeQJVj Hf GdhRjQ,J (B822 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdJeSc HePgH Cgd GdHjJ OQYkG ef GdBaGJ MUjfI s
(3BNQgG (B:s
(3dGRdJ jG SHW GdcQGe MSOkG aGdfGbU GdeScjf ZjQ eMSO eGRGd GdOYGA ddaGVd HHbGA MSGOg hbO JbOe Je GdeQGO HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HBNQgG bQGAI dYHO Gddg Hf GdgGOi Hf EHQGgje Ydi hGdOg GdTGQM GdfGXe SfI (B809 (3g` hcJH GdhGdO UMI GdbQGAIs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs